Security dialogue or talking shop? The Corfu Process under Kazakhstan's OSCE Chairmanship - Andrea Schmitz; Solveig Richter (Stiftung Wissenschaft und Politik (SWP), 2010)
With the Corfu Process, the Organization for Security and Co-operation in Europe (OSCE) wants to regain the key position it was believed to have lost - namely, its role as a forum for broad and inclusive dialogue on security issues from Vancouver to Vladivostok. Yet the challenges are daunting: while the Corfu Process does foster cooperation, it has not yet succeeded in increasing security in Europe. If the basic normative dissent between East and West is not confronted openly but instead just ignored, the risk is high that the process will deteriorate into a trivial discussion group, and that under Kazakhstan's OSCE Chairmanship, it will even undermine the OSCE Acquis. The organisation can only eliminate the deficiencies in the European security architecture if it succeeds in focusing the Corfu Process on a concrete agenda and transforming it into a substantive security dialog
Keywords: 320